Efecto del tipo de muestra en el grado de relación entre diámetro – altura comercial y altura total en las plantas de iryanthera macrophylla (Benth) Warb. En bosque natural Puerto Almendra, Loreto, Perú – 2023 - Fernández Santillan, Reyles Manuel (2024)
The thesis was carried out at the Arboretum of the Faculty of Forestry Sciences, San Juan Bautista, Loreto, Peru. Naturally regenerating plants of Iryanthera macrophylla (Benth) Warb were used. “cumala colorada”; The objective was to determine the relationships between the diameter variables; commercial height and total height of the trees of the species under study. Three samples were used, two of them with diameter class and one random by relationship. The results indicate that the cubic allometric model was the one that presented the best correlation coefficient with 0.997, therefore the degree of relationship was excellent between the diameter and the commercial height; A similar result occurred in the diameter – total height relationship but with a correlation coefficient of 0.996: therefore, the type of sample with 5 diameter classes with a width of 5 cm DBH was the one that presented the best results in this study.